2020
DOI: 10.1371/journal.pone.0241751
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative and anesthesia-related cardiac arrest and mortality rates in Brazil: A systematic review and proportion meta-analysis

Abstract: Introduction Studies have shown that both perioperative and anesthesia-related cardiac arrest (CA) and mortality rates are much higher in developing countries than in developed countries. This review aimed to compare the rates of perioperative and anesthesia-related CA and mortality during 2 time periods in Brazil. Methods A systematic review with meta-analysis of full-text Brazilian observational studies was conducted by searching the Medline, EMBASE, LILACS and SciELO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
(53 reference statements)
3
13
0
1
Order By: Relevance
“…Oxidative stress can be initiated by anaesthetic gases. A study of medical staff exposed to WAGs found the staff exhibited basal DNA damage and elevated IL-17A (Braz et al 2020). The same study also observed these staff had a slightly higher incidence of micronucleus but there no significant change to their levels of oxidative stress biomarkers.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Oxidative stress can be initiated by anaesthetic gases. A study of medical staff exposed to WAGs found the staff exhibited basal DNA damage and elevated IL-17A (Braz et al 2020). The same study also observed these staff had a slightly higher incidence of micronucleus but there no significant change to their levels of oxidative stress biomarkers.…”
Section: Discussionmentioning
confidence: 86%
“…In the study conducted by Braz et al (2020), young medical residents working in operating rooms that did not have adequate scavenging systems and thus were exposed to high concentrations of WAGs for three years, did not exhibit oxidative stress; however, genomic damage and inflammatory states were detected. Similarly, medical staff exposed to high concentrations of anaesthetic gases, even for short durations were found to have elevated levels of IL-8, a proinflammatory chemokine (Chaoul et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Perioperative care has a tremendous role in treating a broad spectrum of diseases in the alleviation of human suffering at all ages ranges from a neonate for a congenital anomaly to nonagenarians for cataract surgery [ 1 ]. However, the quality and safety of perioperative care remain poor particularly in low and middle-income countries where anesthesia-related adverse events were persistent over the years [ [2] , [3] , [4] , [5] , [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%
“…Modern anesthesia in otherwise healthy children above one year of age in developed countries has become very safe due to recent advances in pharmacology, intensive education, and training as well as centralization of care while anesthesia in these children in low-income countries is associated with a high risk of mortality due to lack of basic resources and adequate training of health care providers [ 2 , [11] , [12] , [13] , [14] , [15] , [16] ].…”
Section: Introductionmentioning
confidence: 99%
“…The report by Beecher and Todd helped identify anesthesia safety as a public health problem [14]. The study calls attention to anesthesia mortality risk, as underlined in studies conducted in Europe, Japan, and Brazil [3,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%